FEB-Stacking and FEB-DNN Models for Stock Trend Prediction: A Performance Analysis for Pre and Post Covid-19 Periods - Ghosh, Indranil; Datta Chaudhuri, Tamal (Decision Making: Applications in Management and Engineering, 2021)
In this paper, stock price prediction is perceived as a binary classification problem where the goal is to predict whether an increase or decrease in closing prices is going to be observed the next day. The framework will be of use for both investors and traders. In the aftermath of the Covid-19 pandemic, global financial markets have seen growing uncertainty and volatility and as a consequence, precise prediction of stock price trend has emerged to be extremely challenging. In this background, we propose two integrated frameworks wherein rigorous feature engineering, methodology to sort out class imbalance, and predictive modeling are clubbed together to perform stock trend prediction during normal and new normal times. A number of technical and macroeconomic indicators are chosen as explanatory variables, which are further refined through dedicated feature engineering process by applying Kernel Principal Component (KPCA) analysis. Bootstrapping procedure has been used to deal with class imbalance. Finally, two separate Artificial Intelligence models namely, Stacking and Deep Neural Network models are deployed separately on feature engineered and bootstrapped samples for estimating trends in prices of underlying stocks during pre and post Covid-19 periods. Rigorous performance analysis and comparative evaluation with other well-known models justify the effectiveness and superiority of proposed frameworks.